Autumn, the neglected season in climate change research. (March 2015) - Gallinat, Amanda S.; Primack, Richard B.; Wagner, David L.
Highlights Climate change in autumn shifts times of leaf fall, bird migration, and other events. These shifts change carbon dynamics and can favor invasive species and pathogens. Vulnerable species may be harmed by changing ecological interactions in the autumn. Experiments and new datasets are crucial for improved modeling and management.